Experiencias y vivencias de padres de niños internados en una unidad de terapia intensiva pediátrica de un hospital público de Paraguay - Marcos Antonio Soto; Carlos Miguel Rios-González (Pediatría (Asunción), 2026)
Introduction: The hospitalization of a child in a pediatric intensive care unit (PICU) is a highly stressful experience for parents, with significant emotional, familial, and social repercussions. Understanding their experiences is fundamental to strengthening family-centered care models and guiding psychosocial support interventions in the hospital setting.Objective: To analyze the experiences of parents of children hospitalized in a pediatric intensive care unit of a public hospital in Paraguay during 2024.Methods: A qualitative study with a phenomenological, descriptive, and explanatory design was conducted. Participants were parents of children hospitalized in the PICU of a public referral hospital, recruited between July and August 2024. Data collection was carried out through in-depth, individual, and semi-structured interviews, adapted to the participants' language. The analysis was performed using thematic content analysis with ATLAS.ti software version 24.2.0. Qualitative rigor criteria such as credibility, transferability, reliability, and confirmability were considered. The study was approved by an institutional ethics committee. Results: The parents' experiences were characterized by a high emotional burden, with manifestations of anxiety, fear, helplessness, and guilt predominating. Difficulties related to family organization, economic situation, and work environment emerged. Inequality in access to hospital accommodations was identified, with benefits directed primarily toward mothers, which generated feelings of exclusion and a greater logistical and emotional burden for fathers. The treatment by healthcare staff was mostly rated positively, although demands for more information and psychological support persisted.Conclusion: The experience of parents of children hospitalized in pediatric intensive care is complex and multidimensional, with a significant impact on their emotional well-being. Inequities in institutional support highlight the need to strengthen hospital policies with a gender focus and family-centered care.